Recent Advances in Bacopa Monnieri Research: Neuroprotective Effects and Cognitive Decline Mitigation in Neurodegenerative Diseases with a Focus on Alzheimer’s and Parkinson’s Diseases - Bychowski, Mateusz; Kwaśna, Julia; Górski, Mateusz; Załęska, Adrianna; Kaźmierczyk, Izabela; Lenart, Kacper; Homza, Michał; Zakrzewska, Natalia; Bednarek, Szymon; Kulicka, Joanna (Quality in Sport, 2024)
Background: The global rise in neurodegenerative diseases, including Alzheimer’s and Parkinson’s, has increased interest in natural nootropics such as Bacopa Monnieri. Known for its neuroprotective properties, Bacopa Monnieri has a long history in traditional medicine. This review examines its role in cognitive enhancement, focusing on its effects in neurodegenerative diseases. Methods: Relevant studies published after 2020 were analyzed to assess Bacopa Monnieri’s impact on memory, concentration, and neuroprotection, particularly in Alzheimer’s and Parkinson’s. The review explores mechanisms such as neurotransmitter modulation, reduced neuroinflammation, and enhanced synaptic plasticity. Results: Bacopa Monnieri exhibits neuroprotective effects beneficial for cognitive health and neurodegenerative diseases. It has antioxidant and anti-inflammatory properties, promotes neurogenesis, and increases Brain-Derived Neurotrophic Factor (BDNF). In Alzheimer’s models, it improved cognitive function, reduced amyloid plaques, and prevented Tau aggregation. In Parkinson’s, it enhanced dopaminergic function and reduced neuroinflammation. Despite promising findings, more robust clinical trials are required to confirm its efficacy. Conclusion: Bacopa Monnieri demonstrates potential in neuroprotection and cognitive enhancement, particularly in Alzheimer’s and Parkinson’s. It improves synaptic health and reduces oxidative stress and neuroinflammation. However, larger, high-quality trials are needed to fully establish its therapeutic role in neurodegenerative diseases.